Steric and Electronic Influence of Substituents on the Formation of 1,2,4-Thiadiazolines - JOLLYAMMA, M.; SUJATHA, T.S. (Asian Journal of Chemistry, 2010)
Oxidation of binary mixtures of 1-aryl-3-(2',6'-xylyl)thiourea and thiourea in acidic alcoholic solution yields 3-amino-4-aryl-5-(2',6'- xylyl)imino-Δ2-1,2,4-thiadiazolines. A study of steric and electronic influence of substituents on the formation of 1,2,4-thiadiazolines has also been done. The rearrangement of the bis(formamidine)sulphide to amidinothiourea derivative has been found to be governed by the steric effect.